Johnstown flood [videorecording (DVD)] - Bussler, Mark; Jordan, Patrick; Hooks, Aaron; Dixon, Jennifer; Sposato, Tyler; Dreyfuss, Richard (Inecom Entertainment Company, 2003)
Rumors and fears that the Conemaugh Lake Reservoir had reached its summit and the South Fork Dam might burst were widespread for many years. By Friday, May 31, 1889, in Johnstown, Pennsylvania, it had been raining for a week. Finally at 3:10 pm the center of the dam gave way. Considered the worst flood disaster in the nation's history - 2,209 persons were killed, a countless number of bodies were never found.